Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

How it feels to have a gay or lesbian parent: A book by kids for kids of all ages - Snow, Judith E. (Harrington Park Press, 2004)
Parfois, je rêve d’avoir une baguette magique. Comme ce serait génial de l’agiter et d’éliminer complètement les préjugés, la haine et l’ignorance. Imaginez ce que ce serait de vivre dans un monde comme celui-là. Ce que ça fait d'avoir un parent gay ou lesbien : un livre écrit par des enfants pour les enfants de tous âges donne la parole aux pensées, aux sentiments et aux expériences des enfants, des adolescent.e.s et des jeunes adultes qui ont un parent gay ou lesbien. Dans leurs propres mots, iels parlent ouvertement et franchement de la manière et du moment où iels ont appris l'orientation sexuelle de leurs parents et de l'effet que cela a eu sur ielles et sur leur famille. Leurs histoires font écho aux thèmes des préjugés et du harcèlement, des conflits et de la confusion, de l'adaptation et de l'ajustement, ainsi que de l'espoir de tolérance et d'une famille pouvant exister en harmonie.
Keywords: EDI; identités LGBTQIA2+; jeunesse; parentalité; personnes gay; personnes lesbiennes; pédagogie; thématiques